PENGARUH MODEL 5E LEARNING CYCLE TERHADAP PENINGKATAN PEMAHAMAN KONSEP SAINS - Kelana, Jajang Bayu; Arga, Hana Sakura Putu; Altaftazani, Deden Herdiana; Ruqoyyah, Siti (IKIP Siliwangi Bandung, 2020)
Students' understanding of science concepts must be stimulated by learning activities that make students actively explore their knowledge. One way is through the 5E learning cycle model. This study is to determine the effect of the 5E learning cycle model on understanding the concept of science. The method used is a quasi-experimental method with a sample of 74 students. The instruments used were in the form of test questions for understanding science concepts and observation sheets. The results of this study indicate that the results of the mean difference test in the experimental class and t-test in the control class obtained a P-value (Sig.1-tailed) of 0.000 with a significance level of âˆ = 5%. This means that the P-value <âˆ so that H1 is accepted. Thus, there is a significant increase in understanding the concept of science using the 5E learning cycle and conventional models. The t-test shows the P-value (Sig. 1-tailed) 0,000 <âˆ. It can be concluded that the increase in understanding of science concepts using the 5E learning cycle model is better than conventional.